CD47 blockade reduces ischemia/reperfusion injury in donation after cardiac death rat kidney transplantation. Issue 4 (1st November 2017) - Wang, Xuanchuan; Xu, Min; Jia, Jianluo; Zhang, Zhengyan; Gaut, Joseph P.; Upadhya, Gundumi A.; Manning, Pamela T.; Lin, Yiing; Chapman, William C.
Abstract : Modulation of nitric oxide activity through blockade of CD47 signaling has been shown to reduce ischemia–reperfusion injury (IRI) in various models of tissue ischemia. Here, we evaluate the potential effect of an antibody‐mediated CD47 blockade in a syngeneic and an allogeneic DCD rat kidney transplant model. The donor organ was subjected to 1 hour of warm ischemia time after circulatory cessation, then flushed with a CD47 monoclonal antibody (CD47mAb) in the treatment group, or an isotype‐matched immunoglobulin in the control group. We found that CD47mAb treatment improved survival rates in both models. Serum markers of renal injury were significantly decreased in the CD47mAb‐treated group compared with the control group. Histologically the CD47mAb‐treated group had significantly reduced scores of acute tubular injury and acute tubular necrosis. The expression of biomarkers related to mitochondrial stress and apoptosis also were significantly lower in the CD47mAb‐treated groups. Overall, the protective effects of CD47 blockade were greater in the syngeneic model. Our data show that CD47mAb blockade decreased the IRI of DCD kidneys in rat transplant models. This therapy has the potential to improve DCD kidney transplant outcomes in the human setting. Abstract : Antibody‐mediated CD47 blockade in a rat kidney transplant model of donation after cardiac death improves recipient survival and graft function, and decreases inflammation, oxidative stress, and apoptosis. Xu et al's companion article is onpage 855 .